(untitled) (Biological Sciences - PJSIR, 1995)
Spotted bollworm Eariasfabia Stoll was reared on okra, Abelmoschus esculantus (L.) Moench Meth fruits, as com- pared with cotton leaves, at 30 ± 5°C and 65 ± 5% R.H. The okra fruit was found to be as good as cotton leaves. No significant difference was observed, in incubation period, larval period, pupal period, adult life, numbers of eggs/female and total life cycle, amongst the insects developed on okra fruits or on cotton leaves. The larvae developed on okra fruits took a period of 18 ± 0.882 days and the adults emerged, therefrom showed longevity of a range of 5:5± 3.1456 days at 95% confidence limit, whereas the total incubation period and pupal period was observed at a range of 6.33 ± 0.9996 days and 11±3.3316 days, respectively, for three consecutive generations on okra.